BUSINESS ANALYTICS AS A STRATEGIC RESOURCE FOR THE DEVELOPMENT AND REALIZATION OF THE ENTERPRISE POTENTIAL - MITSENKO, Nataliia; VORONKO, Oksana; BODNARIUK, Volodymyr; KABATSI, Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to develop the methodological foundations of business analytics as a necessary resource for effective strategic management of the enterprise and realization of its potential. The concept of business analytics, its relevance and role for the development of the enterprise is considered. Business analytics is proposed to be considered as a process of collecting, accumulating, processing, analyzing and transforming data into business information necessary for optimizing business processes of the enterprise and strategic management with the help of various methodological tools and software. The principles of building a business analytics system at the enterprise are summarized: organizational, technical, management and economic. The relationship between the business analytics system and the company’s development strategy is presented. It is emphasized that business analytics should take into account the potential opportunities of the enterprise’s resource potential and encourage the appropriate adjustment of business processes that act as tools for strategy implementation. The main tools of descriptive, diagnostic, predictive and recommendatory analytics, which are used in practice when processing data arrays, are presented. Significant differences in the top management’s understanding of the role of business analytics in ensuring the development of enterprises and, accordingly, in the implementation of the results of business analytics in the strategic management of domestic enterprises have been revealed. The dependence of the level of the relationship between business analytics and the company’s development strategy on the availability of a sufficient amount of reliable information, competent personnel and special software is proven. The need for highly qualified business analysts who possess competencies both in working with information bases, in the use of information technologies, and in the field of strategic management has been identified. The Microsoft Power BI complex is proposed for conducting business analytics, taking into account its advantages and services. It is advisable to focus further research on the implementation of modern business analytics methods at enterprises, taking into account the comparative analysis of the capabilities of various business analytics tools, highlighting their advantages and disadvantages.